Penggunaan E-Modul Sains Berbasis QISI (Qur’an Integration-Interconnection and Spiritual Intelligence) untuk Meningkatkan Kemampuan Literasi Sains Digital - Ramadhan, Teuku Muhammad Hary; Dekar, Muhammad; Widyastika, Dinda (Jurnal Kajian Pendidikan IPA, 2025)
This study seeks to enhance students' digital scientific literacy by utilizing science e-modules grounded in Qur’an-based Integration-Interconnection and Spiritual Intelligence (QISI). The participants consisted of 45 students from Luqmanul Hakim IT Junior High School, and the research employed a quantitative method with a pretest-posttest design and purposive sampling technique. The validity results show that the e-module is very valid (87.40%) and very practical (83.83%). N-gain analysis recorded a score of 0.71 (high category), which indicates a significant increase in students' scientific literacy. This e-module is not only effective in integrating spiritual values with science, but also supports higher order thinking skills (HOTS) and increases scientific literacy in the digital era. This study contributes not only to enhancing digital science literacy, but also to preparing Indonesian students to become intellectually competent, spiritually grounded, and well-equipped to face the global challenges of the 21st century. By integrating science and technology with Qur’anic values, the QISI-based e-module offers a relevant, contextual, and transformative learning model for the future of education in Indonesia. Keywords: E-module, Scientific Literacy, Quran, Digital